EMBRACING VALUE-BASED REGULATION TOWARDS SUSTAINABILITY OF THE ISLAMIC FINANCIAL SYSTEM (International Seminar on Syariah and Law (INSLA), 2020)
The legal and regulatory aspects of the Islamic financial system serve as the underlying catalyst of its sustainable development. Revitalizing good governance to achieve Shariah goal is the paramount consideration in the modern Islamic finance other than products development that offers a wide range of wholesale, retail, and trade financing solutions. The value-based intermediation initiative is the vehicle to transform the industry, from profitability and Shariah compliance to impactful services. After more than 30 years of its growth in Malaysia, this study will investigate the value-based regulations applied as a benchmark in the global Islamic finance industry. This study adopts a qualitative method which is mainly library research by analyzingthe relevant works of literature on the subject and data from journal articles, websites,and official reports of the regulators. The study evaluates the legal and Shariah governance frameworks, existing practice,and measures in ensuring effective implementation of Islamic financial system considering the current issues and legal constraints. Findings of this study revealed that Malaysia has a set of value-based regulations, which also lead other countries. Hence, the study suggests that value-based regulations will contribute to the sustainability of the Malaysian Islamic financial system.